Relação da força muscular com equilíbrio estático em idosos – comparação entre pilates e multimodalidades - Bueno, Guilherme Augusto Santos (2018)
Objective: To compare the effect of pilates and multimodalities on muscle strength and balance in the elderly. Methodology: Cross-sectional case-control study, conducted in Goiânia-GO, with 62 elderly women, divided into two groups: Multimodalities and pilates. The manual gripping force (FPM) and the balance were evaluated by Stabilometry. Results: The pilates contributed to higher FPM as well, demonstrated lower ellipse surface, which implies in better balance. However, there was no relationship or prediction of MPF on balance in both groups. Conclusion: pilates promoted greater gains in muscle strength and static balance. However, although muscle strength was the variable with the best result, it did not show a relationship with balance.